Lithium ion secondary battery

By special design on the positive electrode sheet and the negative electrode sheet of the lithium-ion battery, including the convex part design of the positive electrode sheet and the laminated structure and active material arrangement of the negative electrode sheet, the problem of difficult to take into account both the energy density and the charging rate in the prior art is solved. It achieves both high energy density and fast charging performance.

CN119480899APending Publication Date: 2025-02-18ZHEJIANG COSMX BATTERY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411646495.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult for existing lithium-ion batteries to take into account both when pursuing high energy density and fast charging capabilities.

Method used

By providing convex parts on at least one side of the positive electrode sheet and stacking different negative electrode active material layers in the thickness direction of the negative electrode sheet, the arrangement rules of active materials and pores in the negative electrode sheet are regulated to match them and jointly improve the battery. energy density and charging rate.

Benefits of technology

The battery has a high energy density and fast charging performance, avoiding mutual constraints when the energy density and charging rate are increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480899A_ABST
    Figure CN119480899A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion secondary battery. The lithium ion secondary battery comprises a negative plate and a positive plate, the negative plate comprises a negative active material layer, and the negative active material layer comprises a first negative active material layer deviating from the negative current collector and a second negative active material layer close to the negative current collector which are laminated in the thickness direction of the negative plate; the liquid absorption coefficient Y of the negative plate and the vertical distance X from any point in the negative electrode active material layer to the surface of the negative electrode current collector meet the following formula: Y = eX + M-N, the liquid absorption coefficient Y is the ratio of the surface porosity of the section of the negative electrode active material layer which is parallel to the surface of the negative electrode current collector and has the vertical distance X to the average particle size of the negative electrode active material on the section, e is a natural constant, and M is a natural constant. M is 4 to 10, and N is 50 to 4000; at least one side surface of the positive plate is provided with a convex part. The lithium ion secondary battery disclosed by the invention can take both high energy density and relatively good fast charging performance into account.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] With the rapid development of new energy electric vehicles, the performance of lithium-ion batteries as power output systems is particularly important. At present, high energy density and fast charging capabilities have become research hotspots in the industry.

[0003] Energy density and charge rate are important indicators for measuring the performance of lithium-ion batteries. Energy density can be divided into weight energy density (WED, unit: Wh / kg) and volume energy density (VED, unit: Wh / L). Charge rate (Charge Rate) is used to measure the charging speed of lithium-ion batteries. The reciprocal of the time (calculated in hours) required to fully charge a lithium-ion battery is defined as the charge rate (unit: C) of the battery. That is, the shorter the time required to fully charge, the greater the charge rate of the lithium-ion battery. However, the existing technology has the problem that energy density and charge rate cannot be taken into account at the same time.

[0004] Therefore, it is very important to invent a battery that can achieve both high energy density and high charge rate. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that high energy density and high charging rate cannot be taken into account in the prior art, and to provide a lithium-ion secondary battery (hereinafter referred to as a battery). The present invention starts with the structural design of the positive electrode sheet and the negative electrode sheet, so that at least one side of the surface of the positive electrode sheet has a convex portion, and different negative electrode active material layers are stacked in the thickness direction of the negative electrode sheet, and the arrangement of the active material and the pores in the negative electrode sheet is regulated to make the two compatible, and synergistically improve the energy density and charging rate of the battery, which is of great significance for realizing a battery with both high energy density and fast charging performance.

[0006] The standard for measuring the fast charging capability of a lithium-ion battery is to fully charge the battery within the prescribed charging time, then disassemble the battery and observe the surface condition of the negative electrode. If the surface of the negative electrode is golden yellow with no black spots or lithium precipitation, it indicates that the battery has the ability to charge at this rate. Otherwise, it cannot support charging at this rate.

[0007] In the prior art, lithium-ion batteries exhibit poor rate performance at higher energy densities. The inventors of the present invention have found that a convex portion is provided on at least one side of the surface of the positive electrode sheet (the convex portion can be achieved by embossing). This design is conducive to the full infiltration of the electrolyte and the formation of a better ion transmission path without mass loss of the positive electrode active material, thereby improving the rate performance of the battery while ensuring the energy density. However, during the research process, the inventors found that although the provision of a convex portion on at least one side of the surface of the positive electrode sheet is beneficial to improving the rate performance of the lithium-ion battery, the improvement effect is limited.

[0008] Therefore, the inventors of the present invention have conducted a lot of research and found that the reason why the above design has limited improvement on rate performance is that the improvement in energy density and rate performance is not limited to the positive electrode. When the negative electrode's ability to receive lithium ions and its conductivity do not match those of the positive electrode, even if the positive electrode has good capacity and conductivity, the improvement in the overall energy density and rate performance of the battery is limited.

[0009] On this basis, the inventors of the present invention conducted a lot of targeted research and found that by making special settings for the structure of the positive electrode sheet (i.e., making at least one side of the positive electrode sheet have a convex portion), while regulating the arrangement of the active material and pores in the negative electrode sheet, the battery can have both high energy density and charging rate. The reason may be that when the battery is charging, the potential of the part of the negative electrode sheet away from the negative electrode current collector is low, and metallic lithium is easy to precipitate (the reduction potential of lithium is 0V, Li + / Livs graphite), while the potential of the part close to the negative electrode current collector is higher, and metallic lithium is not easy to precipitate. The precipitation of metallic lithium will lead to an increase in dead lithium, which is not conducive to the improvement of battery energy density; and the precipitation of lithium will cause the blockage of lithium ion transmission channels, which is not conducive to the improvement of charging rate. Therefore, in order to avoid lithium precipitation of the negative electrode sheet due to too low potential, the present invention improves the structure of the negative electrode sheet in combination with the potential law of the negative electrode sheet, by stacking different negative electrode active material layers in the thickness direction of the negative electrode sheet, and by adjusting the liquid absorption coefficient Y of the negative electrode sheet, so that the particle size of the negative electrode active material on the negative electrode sheet and the surface porosity of the negative electrode sheet have a certain distribution law along the thickness direction, which effectively improves the wetting effect of the electrolyte on the negative electrode sheet, improves the ion conduction, and makes the prepared battery have both high energy density and good fast charging performance.

[0010] Based on this, the inventors of the present invention proposed the following solution:

[0011] A lithium-ion secondary battery, the lithium-ion secondary battery comprising a positive electrode sheet and a negative electrode sheet; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; the liquid absorption coefficient Y of the negative electrode sheet and the vertical distance X from any point in the negative electrode active material layer to the surface of the negative electrode current collector satisfy: Y=e X+M -N, wherein the liquid absorption coefficient Y is the ratio of the surface porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector and at a vertical distance of X from the surface of the negative electrode collector to the average particle size of the negative electrode active material on the cross section, e is a natural constant, M is 4-10, and N is 50-4000; and the positive electrode sheet has a convex portion on at least one side of the surface.

[0012] Compared with the prior art, the present invention has at least the following beneficial effects:

[0013] First, the positive electrode sheet is embossed so that at least one side of the surface has a convex portion, which is not only conducive to the full infiltration of the electrolyte and forms a better ion transmission path, but also does not cause loss of the positive electrode active material and reduce its energy density, thereby improving the battery's rate performance while ensuring a high energy density;

[0014] Second, different negative electrode active material layers are stacked on the negative electrode sheet along the thickness direction, and the ratio of the surface porosity of the cross section of the negative electrode active material layer in the negative electrode sheet in the thickness direction to the average particle size of the negative electrode active material on the cross section is defined as the liquid absorption coefficient of the negative electrode sheet. The liquid absorption coefficient is used to regulate the arrangement of the active material and the pores in the negative electrode sheet, so that the area far away from the negative electrode current collector has better fast charging performance, and the area close to the negative electrode current collector has high energy density; this design can not only avoid lithium deposition in the area far away from the negative electrode current collector due to too low potential, but also improve the energy density and fast charging performance of the battery;

[0015] Third, the positive electrode sheet and the negative electrode sheet of the present invention have good adaptability. The lack of one of them will lead to incomplete capacity of the battery and mismatch of ion conductivity of the positive and negative electrodes, thereby affecting the overall energy density and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown is a cross-sectional scanning electron microscope (SEM) image of a negative electrode sheet in one embodiment of the present invention.

[0017] Figure 2FIG. 1 is a curve showing the relationship between Y and X in one embodiment of the present invention.

[0018] Figure 3 FIG. 1 is a schematic diagram of a battery housing according to an embodiment of the present invention.

[0019] Figure 4 FIG. 1 is a schematic diagram of the concave and convex portions on the positive electrode sheet in one embodiment of the present invention. DETAILED DESCRIPTION

[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0021] The present invention provides a lithium-ion secondary battery, which comprises a negative electrode sheet and a positive electrode sheet, wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active material layer located on at least one side surface of the negative electrode collector, wherein the negative electrode active material layer comprises a negative electrode active material; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, wherein the first negative electrode active material layer faces away from the negative electrode collector, and the second negative electrode active material layer is close to the negative electrode collector.

[0022] In the present invention, the liquid absorption coefficient Y of the negative electrode sheet and the vertical distance X from any point in the negative electrode active material layer to the surface of the negative electrode current collector satisfy: Y = e X+M -N, wherein the liquid absorption coefficient Y is the ratio of the surface porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector and at a vertical distance of X from the surface of the negative electrode current collector to the average particle size of the negative electrode active material on the cross section, e is a natural constant, M is 4-10, for example, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10; N is 50-4000, for example, 50, 100, 150 , 200, 250, 300, 350, 400, 450, 500, 520, 540, 560, 580, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1700, 1900, 2100, 2300, 2500, 2700, 3000, 3200, 3500, 3700, or 4000.

[0023] In the present invention, at least one side surface of the positive electrode sheet has a convex portion.

[0024] In one embodiment, M is 4.5-6, and N is 100-340.

[0025] In one embodiment, M is 4.9-5.8, and N is 122-329.

[0026] In the present invention, the porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector is 10%-50%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%; the average particle size of the negative electrode active material on the cross section is 1μm-25μm, for example, 1μm, 3μm, 5μm, 7μm, 9μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm or 25μm.

[0027] In one embodiment, the porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector is 18%-38%, and the average particle size of the negative electrode active material on the cross section is 11.3 μm-13.9 μm.

[0028] like Figure 1 FIG. 1 is a cross-sectional scanning electron microscope (SEM) image of a negative electrode sheet in one embodiment of the present invention. Figure 2 FIG. 1 is a curve showing the relationship between Y and X in one embodiment of the present invention. Figure 1 The black vertical bar in the middle is the negative electrode current collector, and the two sides of the negative electrode current collector are the negative electrode active material layers. Figure 2 correspond, Figure 2 The black vertical bar on the Y axis also represents the negative electrode current collector, and X represents the vertical distance from the cross section of the negative electrode active material layer parallel to the negative electrode current collector to the surface of the negative electrode current collector. Figure 2 The curve indicated by 1 is the relationship curve between Y and X, Y = e X+M -N. According to the formula Y = e X+M -N, each point on X can obtain a cross section of the negative electrode active material layer parallel to the negative electrode current collector. Therefore, by adjusting the liquid absorption coefficient Y of the negative electrode sheet, the distribution of the surface porosity of the negative electrode sheet can be adjusted so that it presents a certain regularity along the thickness direction, that is, the more away from the negative electrode current collector, the greater the liquid absorption coefficient, and the closer to the negative electrode current collector, the smaller the liquid absorption coefficient. Through such regulation, the negative electrode sheet can be matched with the positive electrode sheet, so as to achieve the purpose of making the battery have both high rate performance and high energy density.

[0029] The inventors consider that during fast charging, due to the influence of polarization under high current charging, the direction closer to the negative electrode current collector in the negative electrode sheet has a higher potential, and metallic lithium is not easy to precipitate, while the direction farther away from the negative electrode current collector, that is, closer to the surface of the negative electrode sheet, has a lower potential, and lithium precipitation is more likely to occur. Therefore, in the present invention, by regulating the relationship between Y and X, the liquid absorption coefficient Y of the negative electrode active material layer close to the surface of the negative electrode sheet is larger, then the corresponding cross section of the negative electrode active material layer in this area has a larger face porosity, and the particle size of the negative electrode active material is small, the specific surface area is large, and the liquid absorption capacity is strong, so that the electrolyte can better penetrate into the pores of the negative electrode active material layer, ensuring that lithium ions are evenly distributed and embedded, which helps lithium ions to diffuse evenly on the negative electrode surface, reduce polarization and thermal effects during battery charging and discharging, and thus avoid the occurrence of lithium precipitation; while the liquid absorption coefficient Y of the negative electrode active material layer close to the negative electrode sheet current collector is small, and the corresponding cross section has a smaller face porosity, and the particle size of the negative electrode active material in this area is large, which plays a capacity role and improves the energy density.

[0030] In the present invention, the test method of the "face porosity of the cross section of the negative electrode active material layer" is as follows: the negative electrode sheet is cut under an argon ion grinder, and the obtained cross section is subjected to pore filling fitting under a surface filling scanning electron microscope, and the equipment model is Sigma300 / 500; the average particle size of the negative electrode active material can be obtained by conventional testing, for example, first obtaining a high-resolution image through a scanning electron microscope, and then performing particle size measurement and distribution statistics through electron microscope image analysis software such as ImageJ to obtain the average particle size, and the model of the scanning electron microscope is Sigma300 / 500; the above test results can also be obtained by other conventional testing methods in the art.

[0031] In the present invention, the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet is 0.01 mm-16 mm, for example, 0.01 mm, 0.05 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 10 mm, 12 mm, 14 mm or 16 mm, and the spacing of the convex portions is 0 mm-10 mm, for example, 0 mm, 0.1 mm, 0 .3mm, 0.6mm, 0.9, 1.2mm, 1.5mm, 1.8mm, 2mm, 3mm, 4mm, 5mm, 6mm, 8mm or 10mm, and the height of the protrusion is 0.003mm-0.5mm, for example, 0.003mm, 0.005mm, 0.01mm, 0.02mm, 0.05mm, 0.06mm, 0.08mm, 0.1mm, 0.15mm, 0.2mm, 0.25mm, 0.3mm, 0.35mm, 0.4mm, 0.45mm or 0.5mm.

[0032] In one embodiment, the diameter of the orthographic projection of the protrusion on the surface of the positive electrode sheet is 0.01 mm-0.5 mm, the pitch of the protrusions is 0 mm-0.3 mm, and the height of the protrusions is 0.01 mm-0.25 mm.

[0033] In one embodiment, the height of the protrusions is 0.01 mm-0.2 mm, the spacing between the protrusions is 0.1 mm-0.2 mm, and the diameter of the orthographic projection of the protrusions on the surface of the positive electrode sheet is 0.2 mm-0.4 mm.

[0034] In yet another embodiment, the height of the protrusions is 0.05 mm-0.15 mm, the spacing between the protrusions is 0.1 mm-0.2 mm, and the diameter of the orthographic projection of the protrusions on the surface of the positive electrode sheet is 0.2 mm-0.4 mm.

[0035] In the present invention, the height of the convex portion, the spacing between the convex portions and the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet have the conventional meanings in this field. The height of the convex portion refers to the maximum value of the vertical distance from any point on the convex portion to the surface of the positive electrode sheet (the side surface with the convex portion and the part without the convex portion). The spacing between the convex portions refers to: when the orthographic projection of the convex portion on the surface of the positive electrode sheet is a regular circle, the spacing between the convex portions is the difference between the distance between the centers of two adjacent circles and the sum of the radii of the two adjacent circles; when the orthographic projection of the convex portion on the surface of the positive electrode sheet is an irregular circle, the spacing between the convex portions is the difference between the equivalent distance between the centers of regular circles with the same area as the irregular circle and the sum of the radii of regular circles with the same area as the irregular circle. The diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet means: when the orthographic projection of the convex portion on the surface of the positive electrode sheet is a regular circle, the diameter of the convex portion is the diameter of the circle; when the orthographic projection of the convex portion on the surface of the positive electrode sheet is an irregular circle, the diameter of the convex portion is an equivalent diameter of a regular circle with an area equal to that of the irregular circle.

[0036] In the present invention, the convex portion on at least one side of the surface of the positive electrode sheet is obtained by embossing design. The embossing design can form a concave portion on one side of the surface of the positive electrode sheet, and a convex portion on the other side of the surface. This structure is conducive to the full infiltration of the electrolyte and the positive electrode active material, improves the permeability of the electrolyte, forms a good ion transmission path and provides more ion transmission paths, so as to achieve the purpose of improving the rate performance of the lithium-ion battery. In addition, compared with the punching process, this design will not cause loss of active materials and reduce energy density; although the deeper the depth of the concave portion, that is, the higher the height of the convex portion, the more conducive to the infiltration of the electrolyte, so that the cycle performance becomes better, but if the depth of the concave portion of the positive electrode embossing is too large, it will cause damage to the positive electrode current collector, which is not conducive to practical application.

[0037] In one embodiment, the positive electrode sheet has a convex portion on one side surface and a concave portion on the other side surface. Figure 4 The figure shows a schematic diagram of the structure of the concave and convex parts on the positive electrode sheet in one embodiment of the present invention. It can be seen from the figure that the positive electrode sheet has a concave part on one side and a convex part on the other side, and the concave part and the convex part are respectively distributed on both sides of the positive electrode sheet.

[0038] In one embodiment, the position of the concave portion on one side of the surface of the positive electrode sheet corresponds to the position of the convex portion on the other side. “The position of the concave portion on one side of the surface of the positive electrode sheet corresponds to the position of the convex portion on the other side” means: the orthographic projection of the concave portion on the surface of the positive electrode sheet and the orthographic projection of the convex portion on the surface of the positive electrode sheet at least partially overlap; for example, the former (orthographic projection of the concave portion on the surface of the positive electrode sheet) completely covers the latter (projection of the convex portion in the thickness direction of the positive electrode sheet); for another example, the latter completely covers the former; for another example, the two partially overlap.

[0039] In the present invention, the area of ​​the orthographic projection of the concave portion on the surface of the positive electrode sheet is 80%-120% of the area of ​​the orthographic projection of the convex portion on the surface of the positive electrode sheet, for example, 80%, 90%, 100%, 110% or 120%.

[0040] In the present invention, the diameter of the recess is 0.01mm-16mm, for example, 0.01mm, 0.05mm, 0.1mm, 0.15mm, 0.2mm, 0.25mm, 0.3mm, 0.35mm, 0.4mm, 0.45mm, 0.5mm, 0.6mm, 0.8mm, 1mm, 2mm, 3mm, 4mm, 5mm, 10mm, 12mm, 14mm or 16mm, and the spacing of the recess is 0mm-10mm, for example, 0mm, 0.1mm, 0.3mm, 0 .6mm, 0.9, 1.2mm, 1.5mm, 1.8mm, 2mm, 3mm, 4mm, 5mm, 6mm, 8mm or 10mm, and the depth of the recess is 0.003mm-0.5mm, for example, 0.003mm, 0.005mm, 0.01mm, 0.02mm, 0.05mm, 0.06mm, 0.08mm, 0.1mm, 0.15mm, 0.2mm, 0.25mm, 0.3mm, 0.35mm, 0.4mm, 0.45mm or 0.5mm.

[0041] In one embodiment, the diameter of the recess is 0.01 mm-0.5 mm, the spacing between the recesses is 0 mm-0.3 mm, and the depth of the recess is 0.01 mm-0.25 mm.

[0042] In one embodiment, the diameter of the recess is 0.2 mm-0.4 mm, the spacing between the recesses is 0.1 mm-0.2 mm, and the depth of the recess is 0.01 mm-0.2 mm.

[0043] In yet another embodiment, the diameter of the recess is 0.2 mm-0.4 mm, the spacing between the recesses is 0.1 mm-0.2 mm, and the depth of the recess is 0.05 mm-0.15 mm.

[0044] In the present invention, the diameter of the recess, the spacing of the recess and the depth of the recess have the conventional meanings in the art. The diameter of the recess means: when the orthographic projection of the recess on the surface of the positive electrode sheet is a regular circle, the diameter of the recess is the diameter of the circle; when the orthographic projection of the recess on the surface of the positive electrode sheet is an irregular circle, the diameter of the recess is the equivalent diameter of a regular circle with the same area as the irregular circle. The spacing of the recesses refers to: when the orthographic projection of the recesses on the surface of the positive electrode sheet is a regular circle, the spacing of the recesses is the difference between the distance between the centers of two adjacent circles and the sum of the radii of the two adjacent circles; when the orthographic projection of the recesses on the surface of the positive electrode sheet is an irregular circle, the spacing of the recesses is the difference between the equivalent distance between the centers of regular circles with the same area as the irregular circle and the sum of the radii of regular circles with the same area as the irregular circle; the depth of the recess refers to the maximum value of the vertical distance from any point in the recess to the surface of the positive electrode sheet (the side surface with the recess and the part without the recess).

[0045] In the present invention, the diameter of the concave portion, the spacing between the concave portions, the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet and the spacing between the convex portions can be measured by combining a scanning electron microscope with image analysis software, and the depth of the concave portion and the height of the convex portion can be measured using a micrometer. The above test results can also be obtained by other conventional test methods in the art.

[0046] In the present invention, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes first particles and second particles, and the average particle size of the first particles is greater than the average particle size of the second particles.

[0047] In the present invention, the average particle size of the first particles is 0.5μm-3μm, for example, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, 2.5μm or 3μm, and the average particle size of the second particles is 200nm-700nm, for example, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm or 700nm.

[0048] In one embodiment, the average particle size of the first particles is 0.7 μm-2 μm.

[0049] In one embodiment, the average particle size of the first particles is 0.9 μm-1.8 μm, and the average particle size of the second particles is 300 nm-500 nm.

[0050] In the present invention, the positive electrode active material is composed of a combination of first particles with a large average particle size and second particles with a smaller average particle size. This combination, combined with the embossing treatment of the positive electrode sheet, can further enable the positive electrode active material to have a higher compaction density and capacity, thereby achieving the effect of improving the energy density (volume energy density and mass energy density) of the positive electrode sheet.

[0051] In one embodiment, the positive electrode active material includes lithium iron phosphate.

[0052] The negative electrode sheet structure and the positive electrode sheet system of the present invention are highly compatible with lithium iron phosphate, and can significantly improve the fast charging performance of lithium iron phosphate batteries while ensuring a high energy density.

[0053] In the present invention, the average particle size of the first particles and the average particle size of the second particles can be obtained by conventional testing methods in the art, such as using a scanning electron microscope, and the testing method is the same as the test of the average particle size of the negative electrode active material.

[0054] In the present invention, the positive electrode active material includes at least one of the elements C, Ti, V and Mn.

[0055] In the present invention, the mass content of element C in the positive electrode active material is 0.1%-10%, for example, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The mass content of element Ti in the positive electrode active material is 1000ppm-3000ppm, for example, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2600ppm, 2800ppm or 3000ppm. The mass content of element Mn in the positive electrode active material is 200ppm-500ppm, for example, 200ppm, 210ppm, 220ppm, 230ppm, 240ppm, 260ppm, 280ppm, 300ppm, 320ppm, 340ppm, 260ppm, 380ppm, 400ppm, 420ppm, 440ppm, 460ppm, 480ppm or 500ppm. The mass content of element V in the positive electrode active material is 500ppm-1000ppm, for example, 500ppm, 520ppm, 540ppm, 560ppm, 580ppm, 600ppm, 620ppm, 640ppm, 660ppm, 680ppm, 700ppm, 740ppm, 780ppm, 820ppm, 860ppm, 900ppm, 950ppm or 1000ppm.

[0056] In one embodiment, the mass content of element C in the positive electrode active material is 1%-2%.

[0057] In one embodiment, the positive electrode active material includes elements C and Ti.

[0058] In one embodiment, the element C is coated on the surface of lithium iron phosphate.

[0059] The positive electrode active material contains at least one element of C, Ti, V and Mn. The element C can improve the electronic conductivity of the positive electrode active material and reduce the electronic impedance. The elements Ti, V and Mn are transition elements, which can improve the reaction catalytic effect in the electrochemical reaction and enhance the ion conduction ability of the positive electrode sheet, so that the positive electrode active material has a good rate performance. The inventors of the present invention have found that when the elements Ti and C are introduced into the positive electrode active material together, the performance improvement of the positive electrode sheet is more significant. This is due to the synergistic effect generated when the elements Ti and C are introduced together, that is, the introduction of the element Ti optimizes the migration channel of lithium ions, and the introduction of the element C improves the electronic conductivity. On the basis of using positive electrode active materials of different particle sizes to improve the compaction density, the introduction of the elements Ti and C into the positive electrode active material together can further significantly improve the overall performance of the lithium-ion battery.

[0060] In the present invention, the contents of elements C, Ti, V and Mn in the positive electrode active material can be obtained by conventional testing methods in the art, for example, inductively coupled plasma atomic emission spectroscopy (ICP-AES) is used to determine the contents of elements Ti, V and Mn, and X-ray fluorescence spectroscopy (XRF) is used to determine the content of element C.

[0061] In the present invention, the thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:(0.65-19), for example, 1:0.65, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18 or 1:19.

[0062] In one embodiment, a thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:(0.65-10).

[0063] In one embodiment, a thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:(1-4).

[0064] In the present invention, the thickness of the first negative electrode active material layer is 10μm-50μm, for example, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm; the thickness of the second negative electrode active material layer is 30μm-100μm, for example, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm or 100μm.

[0065] In one embodiment, the thickness of the first negative electrode active material layer is 20 μm-40 μm, and the thickness of the second negative electrode active material layer is 40 μm-80 μm.

[0066] In the present invention, the first negative electrode active material layer includes a first negative electrode active material, and the second negative electrode active material layer includes a second negative electrode active material. The average particle size of the first negative electrode active material is 1μm-15μm, for example, 1μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or 15μm; the average particle size of the second negative electrode active material is 5μm-30μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm or 30μm.

[0067] In one embodiment, the average particle size of the first negative electrode active material is 7.2 μm-9.5 μm, and the average particle size of the second negative electrode active material is 13.5 μm-15 μm.

[0068] Under the premise that Y and X satisfy a specific relationship, when the average particle size of the first negative electrode active material and the second negative electrode active material is within a specific range, the energy density and rate performance of the battery can be further improved. The reason is that the particle size of the first negative electrode active material in the first negative electrode active material layer far away from the surface of the negative electrode current collector is small, and its specific surface area is large at this time, which is conducive to the infiltration of the electrolyte, thereby ensuring the uniform diffusion of lithium ions; while the particle size of the second negative electrode active material in the second negative electrode active material layer close to the surface of the negative electrode current collector is large, which is conducive to the capacity of the active material.

[0069] While regulating the average particle size, it is also necessary to regulate the thickness of the first negative electrode active material layer and the second negative electrode active material layer according to the average particle size and material selection so that the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer is within a specific range. If the first negative electrode active material layer is too thick, the electrolyte is not easy to completely infiltrate the second negative electrode active material layer, resulting in difficulty in fully utilizing the capacity. Although the rate performance is good, the energy density is low. When the second negative electrode active material layer is too thick, although the capacity is well utilized, because the first negative electrode active material layer is too thin, the fast charging performance and cycle performance are reduced, and even lithium precipitation may occur.

[0070] In the present invention, the average particle size of the first negative electrode active material and the second negative electrode active material can be measured by conventional methods in the art, such as scanning electron microscopy, and the testing method is the same as the determination of the average particle size of the negative electrode active material.

[0071] In one embodiment, the first negative electrode active material and the second negative electrode active material each independently include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, nano silicon, silicon oxygen, silicon carbon and silicon alloy.

[0072] In the present invention, the strength I of the 004 crystal plane of the first negative electrode active material layer is 1 004 Strength I with 110 crystal plane 1 110 The ratio I 1 004 / I 1 110 is 1-5, for example, 1, 2, 3, 4 or 5, the strength I of the 004 crystal plane of the second negative electrode active material layer 2 004 Strength I with 110 crystal plane 2 110 The ratio I 2 004 / I 2 110 is 5-15, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15.

[0073] In the present invention, the intensity ratio of the 004 crystal plane to the 110 crystal plane can be obtained by conventional testing methods in the art, such as using a powder X-ray diffractometer (XRD) test, and the equipment model of XRD is Shimadzu XRD-6100.

[0074] In the present invention, the powder compaction density of the first negative electrode active material layer under a pressure of 5 tons is 1 g / cm 3 -1.75g / cm 3 , for example 1g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 or 1.75g / cm 3The powder compaction density of the second negative electrode active material layer under a pressure of 5 tons is 1.75 g / cm 3 -2.1g / cm 3 , for example 1.75 g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 , 2.05g / cm 3 or 2.10g / cm 3 .

[0075] In the present invention, the powder compaction density can be obtained using conventional testing methods in the art, such as using an automatic powder compactor with a pressure set to 5 tons for testing, and the equipment model is Sansi Zongheng.

[0076] In the present invention, the powder conductivity of the first negative electrode active material layer under a pressure of 20 kN is 10 S / cm-300 S / cm, for example, 10 S / cm, 15 S / cm, 20 S / cm, 25 S / cm, 30 S / cm, 35 S / cm, 40 S / cm, 45 S / cm, 50 S / cm, 60 S / cm, 70 S / cm, 80 S / cm, 90 S / cm, 100 S / cm, 150 S / cm, 200 S / cm / cm, 250S / cm or 300S / cm, and the powder conductivity of the second negative electrode active material layer under a pressure of 20kN is 200S / cm-600S / cm, for example, 200S / cm, 220S / cm, 240S / cm, 260S / cm, 280S / cm, 300S / cm, 350S / cm, 400S / cm, 450S / cm, 500S / cm, 550S / cm or 600S / cm.

[0077] In one embodiment, the powder conductivity of the first negative electrode active material layer under a pressure of 20 kN is 25 S / cm-295 S / cm, and the powder conductivity of the second negative electrode active material layer under a pressure of 20 kN is 290 S / cm-500 S / cm.

[0078] In the present invention, the powder conductivity can be obtained using conventional testing methods in the art, such as testing using a powder conductivity tester, the equipment model of which is HFD-8100A-300KG.

[0079] In the present invention, the first negative electrode active material layer and the second negative electrode active material layer on the negative electrode sheet use different negative electrode active materials, and their particle size, powder compaction density, powder conductivity and / or powder orientation are different. A negative electrode active material with a smaller particle size, a lower powder compaction density, a lower powder conductivity and / or a smaller powder orientation is used as the first negative electrode active material, which is characterized by a better fast charging rate but a low energy density. A negative electrode active material with a larger particle size, a higher powder compaction density, a higher powder conductivity and / or a larger powder orientation is used as the second negative electrode active material, which is characterized by a higher energy density but a poorer fast charging rate. This setting also conforms to the arrangement law of negative electrode active materials and porosity controlled by limiting the liquid absorption coefficient Y. The first negative electrode active material close to the surface of the negative electrode sheet has good charging rate performance and uniform particle size distribution, and can form larger pores, which is beneficial to the infiltration of electrolyte and improved ion conduction. The second negative electrode active material close to the negative electrode sheet collector has the characteristics of high compaction and forms lower pores, which is beneficial to improve the energy density of the negative electrode sheet. The two work together to enable the lithium-ion battery to maintain good rate performance even at high energy density.

[0080] In the present invention, the particle size Dv of the first negative electrode active material is 1 10 and Dv 1 The ratio of P1 to the second negative electrode active material is Dv 2 10 and Dv 2 The ratio of 90 is P2; the particle size Dv of the positive electrode active material 3 10 and Dv 3 The ratio of 90 is P3; P1, P2 and P3 satisfy P1≥3P3>P2.

[0081] The inventors of the present invention found that when P1, P2 and P3 satisfy P1≥3P3>P2, the prepared lithium-ion battery has good rate performance and energy density, which can be attributed to the fact that when this inequality relationship is satisfied, the first negative electrode active material layer has a narrow particle size distribution and a large porosity, while the second negative electrode active material layer and the positive electrode active material layer have a wide particle size distribution and a high compaction density.

[0082] In the present invention, the particle size distribution Dv of the first negative electrode active material is 1 10 and Dv 1 90. Particle size distribution Dv of the second negative electrode active material 2 10 and Dv 2 90 and the particle size distribution Dv of the positive electrode active material 3 10 and Dv 3 90 can be obtained by conventional testing methods in the art, for example, by using a laser particle size analyzer and measuring by laser diffraction, the equipment model is Mastersize3000.

[0083] In the present invention, the current collector of the positive electrode sheet (i.e., the positive electrode current collector) includes a metal layer and a carbon coating layer on both sides of the metal layer, the metal layer includes aluminum foil, and the thickness of the carbon coating layer on one side of the metal layer is 0.5μm-1.5μm, for example, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm or 1.5μm.

[0084] In the present invention, the thickness of the carbon coating layer can be obtained by conventional testing methods in the art, such as using ion beam cutting to obtain a cross section, and then using cross-section scanning electron microscopy imaging to measure the thickness of the carbon coating layer, and the equipment model is Sigma300 / 500.

[0085] In the present invention, the negative electrode current collector comprises copper foil.

[0086] In one embodiment, the copper foil further contains at least one of the elements Ca, Cr and Zn.

[0087] In the present invention, the mass content of Ca element in the copper foil is 50ppm-100ppm, for example, 50ppm, 52ppm, 54ppm, 56ppm, 58ppm, 60ppm, 62ppm, 66ppm, 70ppm, 75ppm, 80ppm, 85ppm, 90ppm, 95ppm or 100ppm; the mass content of Cr element in the copper foil is 100ppm-200ppm, for example, 100ppm, 102ppm, 104ppm, 106ppm, 108ppm, 110ppm , 115ppm, 120ppm, 125ppm, 130ppm, 140ppm, 150ppm, 160ppm, 170ppm, 180ppm, 190ppm or 200ppm; the mass content of element Zn in the copper foil is not more than 50ppm, for example, 5ppm, 6ppm, 7ppm, 8ppm, 9ppm, 10ppm, 12ppm, 14ppm, 16ppm, 18ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm or 50ppm.

[0088] In the present invention, the copper foil itself helps to improve the electrical conductivity and the affinity with the active material, and enhances the bonding between the current collector and the electrode material; the introduction of other elements into the copper foil can enhance the corrosion resistance of the copper foil at a higher current density, and has the effect of preventing the copper foil from being corroded and dissolved. In particular, Cr helps to enhance the mechanical properties of the copper foil, and Ca and Zn help to improve the electrochemical properties.

[0089] In the present invention, the negative electrode active material layer further includes a negative electrode binder and a negative electrode conductor. The negative electrode binder includes at least one of polyacrylic acid (PAA), sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, polyimide, styrene-butadiene rubber (SBR) and polyvinylidene fluoride, and the negative electrode conductor includes at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.

[0090] In the present invention, the positive electrode sheet further comprises a positive electrode binder and a positive electrode conductor. The positive electrode binder comprises at least one of polyvinylidene fluoride, polyacrylate, polyimide and styrene-butadiene rubber, and the positive electrode conductor comprises at least one of acetylene black, conductive carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.

[0091] In the present invention, the lithium-ion secondary battery further comprises a separator and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet. The separator and the electrolyte can be conventionally selected in the art.

[0092] In the present invention, the lithium-ion secondary battery includes a winding core.

[0093] In one embodiment, the lithium-ion secondary battery includes a housing.

[0094] In one embodiment, the housing is square.

[0095] The inventors of the present invention have found that the square shell battery has a high volume energy density and good cycle performance, and can inhibit battery expansion.

[0096] In the present invention, the housing comprises a shell and a top cover. Figure 3 The figure shows a schematic diagram of the outer shell of a battery in an example of the present invention. It can be seen from the figure that the outer shell has a shell body 21 and a top cover 22. The top cover 22 is provided with a pole 23, an explosion-proof valve 24 and a liquid injection hole 25.

[0097] The lithium ion secondary battery of the present invention is suitable for automotive power batteries and has high energy density and fast charging performance.

[0098] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0099] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0100] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0101] Example

[0102] The following examples are used to illustrate the lithium ion secondary battery of the present invention.

[0103] Embodiment 1:

[0104] Positive electrode preparation:

[0105] The positive electrode active material is lithium iron phosphate (including first particles and second particles, the average particle size of the first particles is 1.5 μm, the average particle size of the second particles is 400 nm, the mass fraction of the first particles in the positive electrode active material is 70%, the mass fraction of the second particles in the positive electrode active material is 30%, and the particle size distribution of the positive electrode active material is Dv 3 10=0.343μm,Dv 3 90=2.648 μm), wherein the lithium iron phosphate has a carbon coating layer and contains element Ti, the mass content of element Ti in the positive electrode active material is 2000 ppm, and the mass content of element C in the positive electrode active material is 2%.

[0106] Lithium iron phosphate, conductive carbon black, multi-walled carbon nanotubes and polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 97.0:0.5:0.5:2.0, and the solid content was set to 65%. The positive electrode slurry was fully mixed and dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12 μm thick carbon-coated aluminum foil (the carbon coating thickness on one side was 1 μm) using a positive electrode coating machine, and double-sided coating was performed. After completion, it was dried in a blast oven, and the dried electrode sheet was calendered in a positive electrode roller press to obtain a positive electrode sheet. The positive electrode sheet was embossed to control the depth of the embossed concave portion to be 0.15 mm, the diameter of the concave portion to be 0.3 mm, and the spacing of the concave portions to be 0.2 mm. A convex portion was formed on the other side of the positive electrode sheet, the height of the convex portion was 0.15 mm, the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet was 0.3 mm, and the spacing of the convex portions was 0.2 mm. The obtained positive electrode sheet was sealed and stored for standby use.

[0107] Negative electrode preparation:

[0108] The first negative electrode active material and the second negative electrode active material are both artificial graphite. Artificial graphite, conductive carbon black, CMC, PAA and SBR are added to deionized water in a mass ratio of 97.0:0.5:0.5:1.5:0.5, and the solid content is set to 50%. Then, they are fully mixed and dispersed to obtain the first negative electrode active material slurry and the second negative electrode active material slurry. Among them, the average particle size of the first negative electrode active material is 7.2μm, and the particle size distribution is Dv1 10=4.9μm、Dv 1 90 = 12.5 μm; the average particle size of the second negative electrode active material is 13.5 μm, and the particle size distribution is Dv 2 10 = 7.3 μm, Dv 2 90=25.4μm; the average particle size of the negative electrode active material is 11.7μm, and the surface porosity of the negative electrode active material layer is 25%-35%.

[0109] Using a double-layer coating process, the first negative electrode active material slurry and the second negative electrode active material slurry are simultaneously coated on a 5μm copper foil by a coating machine. After coating, the negative electrode sheet is dried in a blast oven, and the dried negative electrode sheet is calendered in a negative electrode roller press to obtain a negative electrode sheet, which is sealed and stored for standby use. Among them, the crystal plane strength ratio of the first negative electrode active material layer is 2.4, and the powder compaction density is 1.59g / cm 3 , the powder conductivity is 245S / cm; the crystal plane strength ratio of the second negative electrode active material layer is 8.7, and the powder compaction density is 1.95g / cm 3 , the powder conductivity is 360S / cm; the copper foil contains element Ca, and its content is 80ppm. The thickness ratio of the first negative electrode active material layer (thickness is 24μm) and the second negative electrode active material layer (thickness is 60μm) is 1:2.5.

[0110] Lithium-ion battery assembly:

[0111] The type of lithium-ion battery designed and assembled is a square aluminum shell battery with a length of 208mm, a width of 50mm, and a height of 103mm. The internal winding core is a multi-pole winding design with two winding cores in parallel. The positive and negative electrodes and the diaphragm are cut according to the size specified for the lithium-ion battery. The diaphragm uses a total thickness of 11μm. The diaphragm is located between the positive and negative electrodes. The cut positive and negative electrodes are wound together with the diaphragm on a lithium-ion battery winding machine to form a battery winding core. After that, the square aluminum shell battery is assembled, and then the electrolyte (Shenzhen Xinzhoubang LBC001) is injected and packaged to obtain the battery after injection. The battery schematic is shown as follows Figure 3 shown.

[0112] Lithium-ion battery formation and sorting:

[0113] The battery after injection is charged and formed in the lithium-ion battery formation cabinet, and the upper limit voltage of the formation charge is 3.8V. Then the sorting process is carried out, and the formed battery is discharged first, then charged, and then discharged again. The lower limit voltage of the discharge is 2.0V. The second discharge capacity is the sorting capacity of the battery, and the average voltage during the second discharge process is the nominal voltage of the battery, from which the volume and mass energy density of the battery can be obtained.

[0114] Embodiment 2:

[0115] Positive electrode preparation:

[0116] The positive electrode active material is lithium iron phosphate (including first particles and second particles, the average particle size of the first particles is 1.8 μm, the average particle size of the second particles is 500 nm, the mass fraction of the first particles in the positive electrode active material is 70%, the mass fraction of the second particles in the positive electrode active material is 30%, and the particle size distribution of the positive electrode active material is Dv 3 10=0.361μm、Dv 3 90=3.283 μm), wherein the lithium iron phosphate has a carbon coating layer and contains element Ti, the mass content of element Ti in the positive electrode active material is 1000 ppm, and the mass content of carbon in the positive electrode active material is 1.5%.

[0117] Lithium iron phosphate, conductive carbon black, multi-walled carbon nanotubes and polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 97.0:0.5:0.5:2.0, and the solid content was set to 65%. The mixture was fully mixed and dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12 μm thick carbon-coated aluminum foil (the carbon coating thickness on one side was 0.95 μm) using a positive electrode coating machine. The positive electrode slurry was coated on both sides. After completion, the positive electrode was dried in a blast oven. The dried electrode was calendered in a positive electrode roller press to obtain a positive electrode sheet. The positive electrode sheet was embossed to control the depth of the embossed concave portion to be 0.1 mm, the diameter of the concave portion to be 0.4 mm, and the spacing of the concave portions to be 0.15 mm. A convex portion was formed on the other side of the positive electrode sheet, the height of the convex portion was 0.1 mm, the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet was 0.4 mm, and the spacing of the convex portions was 0.15 mm. The obtained positive electrode sheet was sealed and stored for standby use.

[0118] Negative electrode preparation:

[0119] The first negative electrode active material and the second negative electrode active material are both artificial graphite. Artificial graphite, conductive carbon black, CMC, PAA and SBR are added to deionized water in a mass ratio of 97.0:0.5:0.5:1.5:0.5, and the solid content is set to 50%. Then, they are fully mixed and dispersed to obtain the first negative electrode active material slurry and the second negative electrode active material slurry. Among them, the average particle size of the first negative electrode active material is 8.4μm, and the particle size distribution is Dv 1 10=5.6μm、Dv 1 90 = 15.6 μm; the average particle size of the second negative electrode active material is 14.2 μm, and the particle size distribution is Dv 2 10=7.6μm、Dv 290=27.8μm; the average particle size of the negative electrode active material is 11.3μm, and the surface porosity of the negative electrode active material layer is 27%-38%.

[0120] A double-layer negative electrode coating process is used. The negative electrode slurry of the first negative electrode active material slurry and the negative electrode slurry of the second negative electrode active material slurry are simultaneously coated on a 5μm copper foil by a coating machine. After coating, the negative electrode sheet is dried in a blast oven, and the dried negative electrode sheet is calendered in a negative electrode roller press to obtain a negative electrode sheet, which is sealed and stored for standby use. Among them, the crystal plane strength ratio of the first negative electrode active material layer is 2.8, and the powder compaction density is 1.62g / cm 3 , the powder conductivity is 252S / cm; the crystal plane strength ratio of the second negative electrode active material layer is 9.4, and the powder compaction density is 1.98g / cm 3 , the powder conductivity is 374S / cm; the copper foil contains element Cr, and its content is 150ppm. The thickness ratio of the first negative electrode active material layer (thickness is 40μm) and the second negative electrode active material layer (thickness is 40μm) is 1:1.

[0121] Lithium-ion battery assembly:

[0122] The type of lithium-ion battery designed and assembled is a square aluminum shell battery with a length of 208mm, a width of 50mm, and a height of 103mm. The internal winding core is a multi-pole winding design with two winding cores in parallel. The positive and negative electrodes and the separator are cut according to the size specified for the lithium-ion battery. The separator uses a glue-coated separator with a total thickness of 11μm. The separator is located between the positive and negative electrodes. The cut positive and negative electrodes are wound together with the separator on a lithium-ion battery winding machine into a battery winding core. After that, the square aluminum shell battery is assembled, and then the electrolyte is injected and packaged to obtain a battery after injection. The battery schematic is shown below. Figure 3 shown.

[0123] Lithium-ion battery formation and sorting:

[0124] The battery after injection is charged and formed in the lithium-ion battery formation cabinet, and the upper limit voltage of the formation charge is 3.8V. Then the sorting process is carried out, and the formed battery is discharged first, then charged, and then discharged again. The lower limit voltage of the discharge is 2.0V. The second discharge capacity is the sorting capacity of the battery, and the average voltage during the second discharge process is the nominal voltage of the battery, from which the volume and mass energy density of the battery can be obtained.

[0125] Embodiment 3:

[0126] Positive electrode preparation:

[0127] The positive electrode active material is lithium iron phosphate (including first particles and second particles, the average particle size of the first particles is 0.9 μm, the average particle size of the second particles is 300 nm, the mass fraction of the first particles in the positive electrode active material is 70%, the mass fraction of the second particles in the positive electrode active material is 30%, and the particle size distribution of the positive electrode active material is Dv 3 10=0.399μm、Dv 3 90=3.235 μm), wherein the lithium iron phosphate has a carbon coating layer and contains element Ti, the mass content of element Ti in the positive electrode active material is 3000 ppm, and the mass content of carbon in the positive electrode active material is 1%.

[0128] Lithium iron phosphate, conductive carbon black, multi-walled carbon nanotubes and polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 97.0:0.5:0.5:2.0, and the solid content was set to 65%. The mixture was fully mixed and dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on a 12 μm thick carbon-coated aluminum foil (the carbon coating thickness on one side was 0.92 μm) using a positive electrode coating machine. The positive electrode slurry was coated on both sides. After completion, the positive electrode was dried in a blast oven. The dried electrode was calendered in a positive electrode roller press to obtain a positive electrode sheet. The positive electrode sheet was embossed to control the depth of the embossed concave portion to be 0.05 mm, the diameter of the concave portion to be 0.2 mm, and the spacing of the concave portions to be 0.1 mm. A convex portion was formed on the other side of the positive electrode sheet, the height of the convex portion was 0.05 mm, the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet was 0.2 mm, and the spacing of the convex portions was 0.1 mm. The obtained positive electrode sheet was sealed and stored for standby use.

[0129] Negative electrode preparation:

[0130] The first negative electrode active material and the second negative electrode active material are both artificial graphite. Artificial graphite, conductive carbon black, CMC, PAA and SBR are added to deionized water in a mass ratio of 97.0:0.5:0.5:1.5:0.5, and the solid content is set to 50%. Then, the mixture is fully mixed and dispersed to obtain the first negative electrode active material slurry and the second negative electrode active material slurry. The average particle size of the first negative electrode active material is 9.5 μm, and the particle size distribution is Dv 1 10=6.2μm、Dv 1 90 = 16.5 μm; the average particle size of the second negative electrode active material is 15 μm, and the particle size distribution is Dv 2 10=8.5μm、Dv 2 90=30.5 μm; the average particle size of the negative electrode active material is 13.9 μm, and the surface porosity of the negative electrode active material layer is 18%-25%.

[0131] Using a double-layer coating process, the negative electrode slurry of the first negative electrode active material slurry and the second negative electrode active material layer slurry is simultaneously coated on a 5μm copper foil by a coating machine. After coating, it is dried in a blast oven, and the dried negative electrode sheet is calendered in a negative electrode roller press to obtain a negative electrode sheet, which is sealed and stored for standby use. Among them, the crystal plane strength ratio of the first negative electrode active material layer is 3.5, and the powder compaction density is 1.65g / cm 3 , the powder conductivity is 255S / cm; the crystal plane strength ratio of the second negative electrode active material layer is 9.8, and the powder compaction density is 1.97g / cm 3 , the powder conductivity is 395S / cm; the copper foil contains element Zn, and its content is 40ppm. The thickness ratio of the first negative electrode active material layer (thickness is 20μm) and the second negative electrode active material layer (thickness is 80μm) is 1:4.

[0132] Lithium-ion battery assembly:

[0133] The type of lithium-ion battery designed and assembled is a square aluminum shell battery with a length of 208mm, a width of 50mm, and a height of 103mm. The internal winding core is a multi-pole winding design with two winding cores in parallel. The positive and negative electrodes and the separator are cut according to the size specified for the lithium-ion battery. The separator uses a glue-coated separator with a total thickness of 11μm. The separator is located between the positive and negative electrodes. The cut positive and negative electrodes are wound together with the separator on a lithium-ion battery winding machine into a battery winding core. After that, the square aluminum shell battery is assembled, and then the electrolyte is injected and packaged to obtain a battery after injection. The battery schematic is shown below. Figure 3 shown.

[0134] Lithium-ion battery formation and sorting:

[0135] The battery after injection is charged and formed in the lithium-ion battery formation cabinet, and the upper limit voltage of the formation charge is 3.8V. Then the sorting process is carried out, and the formed battery is discharged first, then charged, and then discharged again. The lower limit voltage of the discharge is 2.0V. The second discharge capacity is the sorting capacity of the battery, and the average voltage during the second discharge process is the nominal voltage of the battery, from which the volume and mass energy density of the battery can be obtained.

[0136] Embodiment 4 group:

[0137] This group is used to verify the influence of the change of the "thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer".

[0138] Based on the configuration of Example 1, the difference is that the thickness ratio between the first negative electrode active material layer and the second negative electrode active material layer is adjusted by changing the thickness of the two layers, as follows:

[0139] In Example 4a, the ratio of the thickness of the first negative electrode active material layer to the second negative electrode active material layer is 1:0.65, wherein the thickness of the first negative electrode active material layer is 50 μm, and the thickness of the second negative electrode active material layer is 32.5 μm; at this time, the surface porosity of the negative electrode active material layer is 30%-40%, the average particle size of the negative electrode active material is 9.7 μm, the crystal plane strength ratio of the first negative electrode active material layer is 2.6, and the crystal plane strength ratio of the second negative electrode active material layer is 8.4.

[0140] In Example 4b, the ratio of the thickness of the first negative electrode active material layer to the second negative electrode active material layer is 1:10, wherein the thickness of the first negative electrode active material layer is 10 μm, and the thickness of the second negative electrode active material layer is 100 μm. Since the thickness of the first negative electrode active material layer is relatively small, the average particle size of the first negative electrode active material should be selected to be smaller. Therefore, Example 4b also has an average particle size of the first negative electrode active material different from that of Example 1, which is 3.5 μm. At this time, the interfacial porosity of the negative electrode active material layer is 15%-25%, the average particle size of the negative electrode active material is 12.6 μm, the crystal plane strength ratio of the first negative electrode active material layer is 1.8, and the powder compaction density is 1.5 g / cm 3 , the powder conductivity is 180S / cm, and the particle size distribution is Dv 1 10=1.8μm、Dv 1 90 = 4.6 μm; the crystal plane intensity ratio of the second negative electrode active material layer is 9.2, and the powder compaction density is 1.95 g / cm 3 , the powder conductivity is 374S / cm.

[0141] Embodiment 5 group:

[0142] This group is used to verify the impact of changes in the "powder compaction density of the first negative electrode active material layer and the second negative electrode active material layer".

[0143] Based on Example 1, the difference is that the powder compaction density of the first negative electrode active material layer and the second negative electrode active material layer is changed, specifically as follows:

[0144] Example 5a: The powder compaction density of the first negative electrode active material layer is 1.55 g / cm 3 The powder compaction density of the second negative electrode active material layer is 1.74 g / cm 3 At this time, the porosity of the negative electrode active material layer is 35%-45%, the crystal plane strength ratio of the first negative electrode active material layer is 2, and the powder conductivity is 235S / cm; the crystal plane strength ratio of the second negative electrode active material layer is 5.6, and the powder conductivity is 290S / cm.

[0145] Example 5b: The powder compaction density of the first negative electrode active material layer is 1.55 g / cm3 The powder compaction density of the second negative electrode active material layer is 2.05 g / cm 3 At this time, the porosity of the negative electrode active material layer is 23%-34%, the crystal plane strength ratio of the first negative electrode active material layer is 2, and the powder conductivity is 235S / cm; the crystal plane strength ratio of the second negative electrode active material layer is 9.6, and the powder conductivity is 420S / cm.

[0146] Example 5c: The powder compaction density of the first negative electrode active material layer is 1.73 g / cm 3 The powder compaction density of the second negative electrode active material layer is 1.74 g / cm 3 At this time, the porosity of the negative electrode active material layer is 32%-43%, the crystal plane strength ratio of the first negative electrode active material layer is 2.7, and the powder conductivity is 267S / cm; the crystal plane strength ratio of the second negative electrode active material layer is 5.6, and the powder conductivity is 290S / cm.

[0147] Embodiment 6 group:

[0148] This group is used to verify the influence of the change of "the average particle size of the first negative electrode active material".

[0149] Based on Example 1, the difference is that the average particle size of the first negative electrode active material is changed, as follows:

[0150] In Example 6a, the average particle size of the first negative electrode active material is 1.2 μm. Since artificial graphite is difficult to reach 1.2 μm, hard carbon is selected as the first negative electrode active material in this embodiment; at this time, the porosity of the negative electrode active material layer is 38%-45%, the average particle size of the negative electrode active material is 10 μm, and the powder compaction density of the first negative electrode active material layer is 1.03 g / cm 3 , the powder conductivity is 25S / cm, and the particle size distribution is Dv 1 10=0.6μm、Dv 1 90=1.5μm.

[0151] In Example 6b, the average particle size of the first negative electrode active material is 7.9 μm; at this time, the porosity of the negative electrode active material layer is 26%-37%, the average particle size of the negative electrode active material is 11.9 μm, the crystal plane intensity ratio of the first negative electrode active material layer is 2.5, the powder conductivity is 269 S / cm, and the particle size distribution is Dv 1 10=5.5μm、Dv 1 90=13.5μm.

[0152] In Example 6c, the average particle size of the first negative electrode active material is 14.6 μm; at this time, the porosity of the negative electrode active material layer is 30%-40%, the average particle size of the negative electrode active material is 13.8 μm, the crystal plane strength ratio of the second negative electrode active material layer is 4.8, the powder conductivity is 295 S / cm, and the particle size distribution is Dv 1 10=9.6μm、Dv 1 90=24.5μm.

[0153] Embodiment 7 group:

[0154] This group is used to verify the influence of the change of "the average particle size of the second negative electrode active material".

[0155] Based on Example 1, the difference is that the average particle size of the second negative electrode active material is changed as follows:

[0156] In Example 7a, the average particle size of the second negative electrode active material is 5.1 μm, and the second negative electrode active material is natural graphite (because the second negative electrode active material has to reach the powder compaction density of this embodiment under the average particle size, artificial graphite is difficult to achieve, so natural graphite is used); at this time, the porosity of the negative electrode active material layer is 15%-25%, the average particle size of the negative electrode active material is 5.7 μm, the crystal plane intensity ratio of the second negative electrode active material layer is 8.5, and the powder compaction density is 1.95 g / cm 3 , the powder conductivity is 450S / cm, and the particle size distribution is Dv 2 10=3.2μm、Dv 2 90=10.5μm.

[0157] In Example 7b, the average particle size of the second negative electrode active material is 18.5 μm; at this time, the porosity of the negative electrode active material layer is 13%-22%, the average particle size of the negative electrode active material is 15.2 μm, the crystal plane strength ratio of the first negative electrode active material layer is 11.3, and the powder compaction density is 2.05 g / cm 3 , the powder conductivity is 430S / cm, and the particle size distribution is Dv 2 10=12.6μm、Dv 2 90=36.5μm.

[0158] In Example 7c, the average particle size of the second negative electrode active material is 29.8 μm; at this time, the porosity of the negative electrode active material layer is 10%-20%, the average particle size of the negative electrode active material is 23.3 μm, the crystal plane strength ratio of the first negative electrode active material layer is 14.8, and the powder compaction density is 2.15 g / cm 3 , the powder conductivity is 500S / cm, and the particle size distribution is Dv 2 10=17.4μm、Dv 290=45.6μm.

[0159] Embodiment 8 group:

[0160] This group is used to verify the impact of changes in the "selection of negative electrode active materials".

[0161] Based on Example 1, the difference is that the selection and composition of the first negative electrode active material and / or the second negative electrode active material used are changed, as follows:

[0162] In Example 8a, the first negative electrode active material layer is graphite 70% + hard carbon 30% (average particle size of 5.4 μm), and the second negative electrode active material is artificial graphite (average particle size of 13.4 μm); at this time, the average particle size of the negative electrode active material is 11.1 μm, and the surface porosity of the negative electrode active material layer is 28%-39%; the crystal plane strength ratio of the first negative electrode active material layer is 1.7, and the powder compaction density is 1.43 g / cm 3 , the powder conductivity is 179S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=3.3μm、Dv 1 90=8.4μm.

[0163] In Example 8b, the first negative electrode active material layer is graphite 55% + hard carbon 45% (average particle size is 4.5 μm), and the second negative electrode active material is artificial graphite (average particle size is 13.5 μm); at this time, the average particle size of the negative electrode active material is 11 μm, and the surface porosity of the negative electrode active material layer is 32%-40%; the crystal plane strength ratio of the first negative electrode active material layer is 1.4, and the powder compaction density is 1.36 g / cm 3 , the powder conductivity is 146S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=2.5μm、Dv 1 90=6.4μm.

[0164] In Example 8c, the first negative electrode active material layer is graphite 40% + hard carbon 60% (average particle size is 3.6 μm), and the second negative electrode active material is artificial graphite (average particle size is 13.5 μm); at this time, the average particle size of the negative electrode active material is 10.7 μm, and the surface porosity of the negative electrode active material layer is 38%-48%; the crystal plane strength ratio of the first negative electrode active material layer is 1.2, and the powder compaction density is 1.28 g / cm 3 , the powder conductivity is 113S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=1.8μm、Dv 1 90=4.5μm.

[0165] In Example 8d, the first negative electrode active material layer is graphite 90% + silicon carbon 10% (average particle size of 7.3 μm), and the second negative electrode active material is artificial graphite (average particle size of 13.5 μm); at this time, the average particle size of the negative electrode active material is 11.7 μm, and the surface porosity of the negative electrode active material layer is 22%-31%; the crystal plane strength ratio of the first negative electrode active material layer is 2, and the powder compaction density is 1.5 g / cm 3 , the powder conductivity is 222S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=5μm、Dv 1 90=12.6μm.

[0166] In Example 8e, the first negative electrode active material layer is graphite 80% + silicon carbon 20% (average particle size is 7.4 μm), and the second negative electrode active material is artificial graphite (average particle size is 13.4 μm); at this time, the average particle size of the negative electrode active material is 11.7 μm, and the surface porosity of the negative electrode active material layer is 20%-30%; the crystal plane strength ratio of the first negative electrode active material layer is 1.9, and the powder compaction density is 1.54 g / cm 3 , the powder conductivity is 196S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=5μm、Dv 1 90=12.7μm.

[0167] In Example 8f, the first negative electrode active material layer is graphite 80% + silicon carbon 20% (average particle size is 7.5 μm), and the second negative electrode active material is graphite 80% + silicon carbon 20% (average particle size is 12.5 μm); at this time, the average particle size of the negative electrode active material is 11.1 μm, and the surface porosity of the negative electrode active material layer is 16%-25%; the crystal plane strength ratio of the first negative electrode active material layer is 1.8, and the powder compaction density is 1.45 g / cm 3 , the powder conductivity is 198S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=5.1μm、Dv 1 90 = 12.9 μm; the crystal plane intensity ratio of the second negative electrode active material layer is 7.5, and the powder compaction density is 1.85 g / cm 3 , the powder conductivity is 290S / cm; the particle size distribution of the second negative electrode active material is Dv 2 10=7μm、Dv 2 90=24.4μm.

[0168] Embodiment 9 group:

[0169] This group is used to verify the impact of changes in the "specifications and parameters of the convex and concave parts obtained by the positive electrode sheet embossing process".

[0170] Based on Example 1, the difference is that the parameters of the positive electrode embossing process are changed by changing the diameter, height, spacing of the convex part and the diameter, depth, spacing of the concave part, as follows:

[0171] In Example 9a, the diameter of the concave portion is 0.02 mm, the spacing between the concave portions is 0.2 mm, and the depth of the concave portion is 0.15 mm. The diameter of the projection of the convex portion on the surface of the positive electrode sheet is 0.02 mm, the spacing between the convex portions is 0.2 mm, and the height of the convex portion is 0.15 mm.

[0172] In Example 9b, the diameter of the concave portion is 0.48 mm, the spacing between the concave portions is 0.2 mm, and the depth of the concave portion is 0.15 mm. The diameter of the projection of the convex portion on the surface of the positive electrode sheet is 0.48 mm, the spacing between the convex portions is 0.2 mm, and the height of the convex portion is 0.15 mm.

[0173] In Example 9c, the diameter of the concave portion is 0.3 mm, the spacing between the concave portions is 0.02 mm, and the depth of the concave portion is 0.15 mm. The diameter of the projection of the convex portion on the surface of the positive electrode sheet is 0.3 mm, the spacing between the convex portions is 0.02 mm, and the height of the convex portion is 0.15 mm.

[0174] In Example 9d, the diameter of the concave portion is 0.3 mm, the spacing between the concave portions is 0.29 mm, and the depth of the concave portion is 0.15 mm. The diameter of the projection of the convex portion on the surface of the positive electrode sheet is 0.3 mm, the spacing between the convex portions is 0.29 mm, and the height of the convex portion is 0.15 mm.

[0175] In Example 9e, the diameter of the concave portion is 0.3 mm, the spacing between the concave portions is 0.2 mm, the depth of the concave portion is 0.01 mm, the diameter of the convex portion (the orthographic projection of the convex portion on the surface of the positive electrode sheet) is 0.3 mm, the spacing between the convex portions is 0.2 mm, and the height of the convex portion is 0.01 mm.

[0176] In Example 9f, the diameter of the concave portion is 0.3 mm, the spacing between the concave portions is 0.2 mm, and the depth of the concave portion is 0.2 mm. The diameter of the projection of the convex portion on the surface of the positive electrode sheet is 0.3 mm, the spacing between the convex portions is 0.2 mm, and the height of the convex portion is 0.2 mm.

[0177] Example 10 Group:

[0178] This group is used to verify the impact of changes in the "average particle size of the first particles and the second particles in the positive electrode active material".

[0179] Based on Example 1, the difference is that the average particle size of the first particles and / or the second particles is changed as follows:

[0180] In Example 10a, the average particle size of the first particles is 0.73 μm, and the average particle size of the second particles is 400 nm.

[0181] In Example 10b, the average particle size of the first particles is 1.95 μm, and the average particle size of the second particles is 400 nm.

[0182] In Example 10c, the average particle size of the first particles is 1.5 μm, and the average particle size of the second particles is 205 nm.

[0183] In Example 10d, the average particle size of the first particles is 1.5 μm, and the average particle size of the second particles is 695 nm.

[0184] Embodiment 11 group:

[0185] This group of examples is used to verify the impact of changes in "elements contained in the positive electrode active material, namely, lithium iron phosphate".

[0186] Based on Example 1, the difference is that the element type or element content in the extremely active material, namely, lithium iron phosphate, is changed, as follows:

[0187] In Example 11a, the positive electrode active material, lithium iron phosphate, contains element V, and the content of element V in the positive electrode active material is 800 ppm; the lithium iron phosphate contains a carbon coating layer, and the content of element C in the positive electrode active material is 2%.

[0188] In Example 11b, the positive electrode active material, lithium iron phosphate, contains element Mn, and the content of element Mn in the positive electrode active material is 350 ppm; the lithium iron phosphate contains a carbon coating layer, and the content of element C in the positive electrode active material is 2%.

[0189] In Example 11c, the positive electrode active material, lithium iron phosphate, contains element Ti, and the content of element Ti in the positive electrode active material is 2000 ppm; the lithium iron phosphate contains a carbon coating layer, and the content of element C in the positive electrode active material is 0.12%.

[0190] In Example 11d, the positive electrode active material, lithium iron phosphate, contains element Ti, and the content of element Ti in the positive electrode active material is 2000 ppm; the lithium iron phosphate contains a carbon coating layer, and the content of element C in the positive electrode active material is 9.5%.

[0191] Embodiment 12 group:

[0192] This group is used to verify the impact of changes in the "thickness of the carbon coating layer on the positive electrode current collector".

[0193] Based on Example 1, the difference is that the thickness of the single-sided carbon coating layer on the surface of the positive electrode current collector is changed, as follows:

[0194] In Example 12a, the thickness of the carbon coating layer on one side of the positive electrode current collector surface is 0.53 μm.

[0195] In Example 12b, the thickness of the carbon coating layer on one side of the positive electrode current collector surface is 1.45 μm.

[0196] Embodiment 13 group:

[0197] This group is used to verify whether the impact of the "inequality P1≥3P3>P2" is met.

[0198] Based on Example 1, the difference is that Dv is changed 1 10 and Dv 1 90 or change Dv 2 10 and Dv 2 90, by changing the particle size distribution of the first negative electrode active material and the second negative electrode active material, as follows:

[0199] Example 13a: The particle size distribution of the first negative electrode active material is Dv 1 10=4.8μm、Dv 1 90 = 15 μm, the particle size distribution of the second negative electrode active material is Dv 2 10=7.3μm、Dv 2 90 = 25.4 μm, the particle size distribution of the positive electrode active material is Dv 3 10=0.343μm、Dv 3 90 is =2.648μm, at this time P1=0.32, P2=0.287, P3=0.13, P1<3P3, and the inequality is not satisfied.

[0200] Example 13b: The particle size distribution of the first negative electrode active material is Dv 1 10=4.9μm、Dv 1 90 = 12.5 μm, the particle size distribution of the second negative electrode active material is Dv 2 10=10μm、Dv 2 90 = 25 μm, the particle size distribution of the positive electrode active material is Dv 3 10=0.343μm、Dv 3 90=2.648μm, at this time P1=0.392, P2=0.4, P3=0.13, 3P3<P2, the inequality is not satisfied.

[0201] The verification of the inequality P1≥3P3>P2 is shown in Table 1.

[0202] Comparative Example 1:

[0203] Based on Example 1, the difference is that the positive electrode is not subjected to embossing process, and the rest is consistent with Example 1.

[0204] Comparative Example 2:

[0205] Based on Example 1, the difference is that the negative electrode is coated with a single layer, specifically, the first negative electrode active material slurry and the second negative electrode active material slurry are mixed in a certain mass ratio to obtain a negative electrode slurry, and the coating is performed so that the particle size distribution of the negative electrode active material is Dv10=7.5μm, Dv50=13.8μm, Dv90=23.6μm, and the thickness of the negative electrode active material layer is 84μm. At this time, the interfacial porosity of the negative electrode active material layer is 14.52%-15.22%, the crystal plane strength ratio is 6.4, and the powder compaction density is 1.93g / cm 3 , the powder conductivity is 320S / cm.

[0206] Comparative Example 3 Group:

[0207] This group of comparative examples is used to verify that the relationship curve between Y and X, that is, Y = e X+M -N" is as follows:

[0208] Comparative Example 3a is based on Example 1, except that the powder compaction density of the first negative electrode active material layer is 2.05 g / cm 3 The powder compaction density of the second negative electrode active material layer is 1.65 g / cm 3 The average particle size of the first negative electrode active material was 16.7 μm, and the particle size of the second negative electrode active material was 5.2 μm.

[0209] At this time, the crystal plane intensity ratio of the first negative electrode active material layer is 8.6, and the powder conductivity is 483S / cm, the crystal plane intensity ratio of the second negative electrode active material layer is 1.5, and the powder conductivity is 228S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=11.3μm、Dv 1 90 = 40.6 μm, the particle size distribution of the second negative electrode active material is Dv 2 10=3.7μm、Dv 1 90=9.6 μm, the average particle size of the negative electrode active material is 8.94 μm, and the porosity of the negative electrode active material layer is 10%-12%.

[0210] Comparative Example 3b is based on Example 1, except that the powder compaction density of the first negative electrode active material layer is 1.9 g / cm 3 The powder compaction density of the second negative electrode active material layer is 2.1 g / cm 3 The average particle size of the first negative electrode active material was 17.9 μm, and the particle size of the second negative electrode active material was 22.8 μm.

[0211] At this time, the crystal plane intensity ratio of the first negative electrode active material layer is 9.6, and the powder conductivity is 368S / cm, the crystal plane intensity ratio of the second negative electrode active material layer is 12.8, and the powder conductivity is 405S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=11.3μm、Dv 1 90 = 40.6 μm, the particle size distribution of the second negative electrode active material is Dv 2 10=3.7μm、Dv 1 90=9.6 μm, the average particle size of the negative electrode active material is 21.4 μm, and the porosity of the negative electrode active material layer is 15%-16%.

[0212] Comparative Example 3c is based on Example 1, except that the powder compaction density of the first negative electrode active material layer is 1.95 g / cm 3 The powder compaction density of the second negative electrode active material layer is 1.95 g / cm 3 The average particle size of the first negative electrode active material was 10.7 μm, and the particle size of the second negative electrode active material was 11.5 μm.

[0213] At this time, the crystal plane intensity ratio of the first negative electrode active material layer is 8, the powder conductivity is 345S / cm, the crystal plane intensity ratio of the second negative electrode active material layer is 8.5, and the powder conductivity is 355S / cm; the particle size distribution of the first negative electrode active material is Dv 1 10=11.3μm、Dv 1 90 = 40.6 μm, the particle size distribution of the second negative electrode active material is Dv 2 10=3.7μm、Dv 1 90=9.6 μm, the average particle size of the negative electrode active material is 11.27 μm, and the porosity of the negative electrode active material layer is 20%-21%.

[0214] In the above embodiments and comparative examples, the powder compaction density refers to the powder compaction density under a pressure of 5 tons, and the powder conductivity refers to the powder conductivity under a pressure of 20 kN.

[0215] Test example:

[0216] 1. Determination of the relationship curve between liquid absorption coefficient Y and X

[0217] By testing the distribution of the porosity of the negative electrode sheet and the cross section parallel to the negative electrode current collector, combined with the particle size distribution of the negative electrode active material in the negative electrode active material layer on the cross section, some values ​​of the liquid absorption coefficient Y under the change of X can be calculated, and the relationship curve between the liquid absorption coefficient Y and X can be obtained through formula fitting. The specific values ​​and fitting results are shown in Table 2.

[0218] 2. Lithium-ion secondary battery test:

[0219] (1) Fast charging cycle test:

[0220] A blue electric test cabinet was used to carry out charge and discharge tests on the batteries prepared in the embodiments and comparative examples. A suitable charging system was found through battery simulation technology, and the charging time of 10%-80% SOC was controlled to be 10 min (SOC is the battery state of charge, the fully charged battery is 100% SOC, and the empty battery is 0% SOC), and the discharge time was 60 min. This charge and discharge system was used to carry out charge and discharge cycle tests on the batteries. One charge and one discharge is called one cycle. After 50 charge and discharge cycle tests, the battery was charged to 100% SOC, the battery was removed for disassembly, and the lithium deposition state on the surface of the negative electrode was observed. If no lithium deposition occurs, it means that the fast charging capacity meets the 10 min fast charging cycle. If lithium deposition occurs, it means that the fast charging capacity cannot meet the 10 min fast charging cycle.

[0221] (2) Energy density test:

[0222] Use a blue power test cabinet to charge the battery at a constant current of 0.33C with an upper voltage limit of 3.8V, then perform constant voltage charging with a cutoff current of 0.05C, let it stand for 10 minutes, and then discharge it to 2.0V at 0.33C. Record the discharge capacity as C, unit: Ah, the discharge energy as E, unit: Wh, and the volume of the battery as V, unit: L, and the mass as W, unit: Kg. Therefore, the battery volume energy density is D1=E / V, unit: Wh / L, and the mass energy density is D2=E / W, unit: Wh / Kg.

[0223] (3) Capacity retention test:

[0224] Using the fast charge cycle test method in (1), the discharge capacity during the first cycle is recorded as C1, and the battery discharge capacity after the 1000th cycle is recorded as C2. The capacity retention rate of the battery after 1000 charge and discharge cycles is P = C2 / C1×100%.

[0225] The test results are shown in Table 3.

[0226] Table 1:

[0227]

[0228]

[0229] Table 2:

[0230]

[0231]

[0232] Table 3

[0233]

[0234]

[0235] It can be seen from Table 3 that the lithium ion secondary battery prepared by the present invention can have both high energy density and fast charging performance compared with the comparative example.

[0236] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises a negative electrode sheet and a positive electrode sheet; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, wherein the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; The liquid absorption coefficient Y of the negative electrode sheet and the vertical distance X from any point in the negative electrode active material layer to the surface of the negative electrode current collector satisfy: Y = e X+M -N, wherein the liquid absorption coefficient Y is the ratio of the porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector and at a vertical distance of X from the surface of the negative electrode current collector to the average particle size of the negative electrode active material on the cross section, e is a natural constant, M is 4-10, and N is 50-4000; At least one side surface of the positive electrode sheet has a convex portion.

2. The lithium ion secondary battery according to claim 1, wherein M is 4.5-6, N is 100-340; preferably, M is 4.9-5.8, N is 122-329; and / or, the porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector is 10%-50%, and the average particle size of the negative electrode active material on the cross section is 1 μm-25 μm; Preferably, the porosity of the cross section of the negative electrode active material layer parallel to the negative electrode current collector is 18%-38%, and the average particle size of the negative electrode active material on the cross section is 11.3 μm-13.9 μm.

3. The lithium ion secondary battery according to claim 1 or 2, wherein: The height of the convex portion is 0.01mm-0.25mm, the spacing between the convex portions is 0mm-0.3mm, and the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet is 0.01mm-0.5mm; preferably, the height of the convex portion is 0.05mm-0.15mm, the spacing between the convex portions is 0.1mm-0.2mm, and the diameter of the orthographic projection of the convex portion on the surface of the positive electrode sheet is 0.2mm-0.4mm; And / or, the surface of one side of the positive electrode sheet has the convex portion, and the surface of the other side of the positive electrode sheet has a concave portion, the diameter of the concave portion is 0.01mm-0.5mm, the spacing between the concave portions is 0mm-0.3mm, and the depth of the concave portion is 0.01mm-0.25mm; preferably, the diameter of the concave portion is 0.2mm-0.4mm, the spacing between the concave portions is 0.1mm-0.2mm, and the depth of the concave portion is 0.05mm-0.15mm.

4. The lithium ion secondary battery according to claim 3, wherein: The positive electrode sheet includes a positive electrode active material, the positive electrode active material includes first particles and second particles, and the average particle size of the first particles is greater than the average particle size of the second particles; Preferably, the positive electrode active material includes lithium iron phosphate; Preferably, the average particle size of the first particles is 0.5 μm-3 μm, and the average particle size of the second particles is 200 nm-700 nm; More preferably, the average particle size of the first particles is 0.9 μm-1.8 μm, and the average particle size of the second particles is 300 nm-500 nm.

5. The lithium ion secondary battery according to claim 4, wherein: The positive electrode active material comprises at least one of the elements C, Ti, V and Mn; Preferably, the positive electrode active material comprises elements C and Ti; Preferably, element C is coated on the surface of lithium iron phosphate.

6. The lithium ion secondary battery according to claim 5, wherein: The mass content of element C in the positive electrode active material is 0.1%-10%, preferably 1%-2%; And / or, the mass content of element Ti in the positive electrode active material is 1000ppm-3000ppm; And / or, the mass content of element Mn in the positive electrode active material is 200ppm-500ppm; And / or, the mass content of element V in the positive electrode active material is 500ppm-1000ppm.

7. The lithium ion secondary battery according to claim 1 or 2, wherein: The thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:(0.65-19); And / or, the first negative electrode active material layer includes a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material, the first negative electrode active material has an average particle size of 1 μm-15 μm, and the second negative electrode active material has an average particle size of 5 μm-30 μm; Preferably, the first negative electrode active material and the second negative electrode active material each independently include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, nano silicon, silicon oxygen, silicon carbon and silicon alloy.

8. The lithium ion secondary battery according to claim 1 or 2, wherein: The strength I of the 004 crystal plane of the first negative electrode active material layer 1 004 Strength I with 110 crystal plane 1 110 The ratio I 1 004 / I 1 110 is 1-5, the intensity I of the 004 crystal plane of the second negative electrode active material layer 2 004 Strength I with 110 crystal plane 2 110 The ratio I 2 004 / I 2 110 5-15; And / or, the powder compaction density of the first negative electrode active material layer under a pressure of 5 tons is 1 g / cm 3 -1.75g / cm 3 The powder compaction density of the second negative electrode active material layer under a pressure of 5 tons is 1.75 g / cm 3 -2.1g / cm 3 ; And / or, the powder conductivity of the first negative electrode active material layer under a pressure of 20 kN is 10 S / cm-300 S / cm, and the powder conductivity of the second negative electrode active material layer under a pressure of 20 kN is 200 S / cm-600 S / cm.

9. The lithium ion secondary battery according to claim 1 or 2, wherein: The first negative electrode active material layer includes a first negative electrode active material, and the particle size Dv of the first negative electrode active material is 1 10 and Dv 1 90 is P1, the second negative electrode active material layer includes a second negative electrode active material, and the particle size Dv of the second negative electrode active material is 2 10 and Dv 2 The positive electrode sheet includes a positive electrode active material, and the particle size Dv of the positive electrode active material is 3 10 and Dv 3 The ratio of 90 is P3; P1, P2 and P3 satisfy P1≥3P3>P2.

10. The lithium ion secondary battery according to claim 1 or 2, wherein: The current collector of the positive electrode sheet comprises a metal layer and a carbon coating layer on both sides of the metal layer, the metal layer comprises an aluminum foil, and the thickness of the carbon coating layer on one side of the metal layer is 0.5 μm-1.5 μm; And / or, the negative electrode current collector comprises copper foil; Preferably, the copper foil further contains at least one of the elements Ca, Cr and Zn.

Citation Information

Cited By

  • Battery, battery assembly and electric equipment

    CN121215848A

  • A battery, a battery assembly and an electric device

    CN121215848B